Models for reducing the risk of critical networked infrastructures. (29th August 2011) - Medal, Hugh; Sharp, Stevenson J.; Pohl, Ed; Rainwater, Chase; Mason, Scott J.
In this paper, we review the literature studying how to reduce the disruption risk to critical networked infrastructures. This is an important area of research because huge consequences result from infrastructure disruptions. As a result, this research area has grown a lot in the last decade. In this review we discuss articles from the literature, place them into categories, and suggest topics for future research. Our review shows that although this area is growing in popularity, there are still many important opportunities for future work.